2020
DOI: 10.1101/2020.11.16.20232850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 employment shocks on suicide and safety net use: An early-stage investigation

Abstract: This paper examines whether the COVID-19-induced employment shock has increased suicides and the utilization of means-tested poverty alleviation programs in the first eight months of the COVID-19 crisis. We exploit plausibly exogenous regional variation in the magnitude of the employment shock in Japan and adopt a difference-in-differences (DID) research design to identify the employment-shock impact. Our preferred point estimates suggest that a one-percentage-point decrease in the employment rate in the secon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…15 Three separate studies used a similar approach to analyse Japanese suicide statistics: one considered children and adolescents only and found no evidence of an increase; 16 and the other two considered all age groups and identified a decrease in the pandemic's early stages, 17 but highlighted an upswing in July, 2020. 17,18 Only five studies-from Greece, 19 Queensland in Australia, 20 Massachusetts in the USA, 21 Peru, 22 and Japan 23 -have used official data and accounted for temporal trends. The studies in Greece, Queensland, and Massachusetts found that the observed and expected numbers of suicides did not differ after pandemic responses were introduced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Three separate studies used a similar approach to analyse Japanese suicide statistics: one considered children and adolescents only and found no evidence of an increase; 16 and the other two considered all age groups and identified a decrease in the pandemic's early stages, 17 but highlighted an upswing in July, 2020. 17,18 Only five studies-from Greece, 19 Queensland in Australia, 20 Massachusetts in the USA, 21 Peru, 22 and Japan 23 -have used official data and accounted for temporal trends. The studies in Greece, Queensland, and Massachusetts found that the observed and expected numbers of suicides did not differ after pandemic responses were introduced.…”
Section: Introductionmentioning
confidence: 99%
“…22 The Japanese study confirmed fluctuations in suicides and identified a positive association between pandemic-induced employment shocks and suicides. 23 The evidence so far is insufficient to indicate what the effect of COVID-19 on suicides has been or will be. It is…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, studies from Greece, Australia (Queensland) and the USA (Massachusetts) have demonstrated stability in suicide rates, whereas a study from Peru reported a decline in suicides following the implementation of a pandemic-related lockdown (76)(77)(78)(79). Another study from Japan demonstrated fluctuations in suicide rates and highlighted their association with pandemic-induced employment shocks (80).…”
Section: Suicidal Behaviors In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%